Relevance of structural damage in the sacroiliac joints for the functional status and spinal mobility in patients with axial spondyloarthritis: results from the German Spondyloarthritis Inception Cohort - Mikhail Protopopov; Joachim Sieper; Hildrun Haibel; Joachim Listing; Martin Rudwaleit; Denis Poddubnyy (Arthritis Research & Therapy, 2017)
Abstract Background Functional status and spinal mobility in patients with axial spondyloarthritis (axSpA) are known to be determined both by disease activity and by structural damage in the spine. The impact of structural damage in the sacroiliac joints (SIJ) on physical function and spinal mobility in axSpA has not been studied so far. The objective of the study was to analyze the impact of radiographic sacroiliitis on functional status and spinal mobility in patients with axSpA. Methods In total, 210 patients with axSpA were included in the analysis. Radiographs of SIJ obtained at baseline and after 2 years of follow up were scored by two trained readers according to the modified New York criteria grading system (grade 0–4). The mean of two readers’ scores for each joint and a sum score for both SIJ were calculated for each patient giving a sacroiliitis sum score between 0 and 8. The Bath Ankylosing Spondylitis Functional Index (BASFI) and Bath Ankylosing Spondylitis Metrology Index (BASMI) at baseline and after 2 years were used as outcome measures. Results Longitudinal mixed model analysis adjusted for structural damage in the spine (modified Stoke Ankylosing Spondylitis Spine Score - mSASSS), disease activity (Bath Ankylosing Spondylitis Disease Activity Index - BASDAI and C-reactive protein level) and gender, revealed an independent association of the sacroiliitis sum score with the BASFI: b = 0.10 (95% CI 0.01–0.19) and the BASMI: b = 0.12 (95% CI 0.03–0.21), respectively, indicating that change by one radiographic sacroiliitis grade in one joint is associated with BASFI/BASMI worsening by 0.10/0.12 points, respectively, independently of disease activity and structural damage in the spine. Conclusion Structural damage in the SIJ might have an impact on functional status and spinal mobility in axSpA independently of spinal structural damage and disease activity. Trial registration ClinicalTrials.gov, NCT01277419 . Registered on 14 January 2011.